Draft Annual Plan 1968-1969 Government of Andhra Pradesh - Planning Commission (Planning Commission, 1968)
The Project in execution comprises and location the construction of a masonry dam (FRL+546) with crest gates in spillway upto +590 across the Krishna River, and two canals one on the Right side for a length of 126 miles and another on the Left side for a length of 111 miles to irrigate in all 22 lakh acres including 1.5 lakh acres of second crop under Krishna delta in the Nalgonda, Khammam, Krishna, Guntur Kurnooland Nellore districts of Andhra Pradesh
Government of Andhra Pradesh Planning Department
Government of Andhra Pradesh Planning Department